Identity in the Society of the 21st Century Advocating for Electronic Governance - Modern Information Society or Modernization of Information Society? - Szakálné Szabó, Zita (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
We can evaluate the quality of the state’s activities primarily through the functioning of the public administration, and if clients often feel that administrators are in a position of power, this can greatly affect the dynamics of their relationship. With the formation of communities, the range of issues that affected the entire society and the effective solution of which was felt to be everyone’s, naturally appeared. The citizen’s expectation is that administration should be simple, fast and should ensure equal treatment. The relationship between public administration and the client is very important, as the quality of public services and the satisfaction of citizens largely depend on how public administration communicates with clients. Therefore, it is important that public administration takes into account the needs and expectations of customers in every case in order to improve customer satisfaction. In parallel with the trust of the client, public administration will be efficient. Nevertheless, in today’s customer-friendly public administration the question is how well electronic administration meets the expectations and possibilities of citizens. In what way do the clerks who perform office work serve according to the possibilities available to them?